Effect on mortality of increasing the cutoff blood glucose concentration for initiating hypoglycaemia treatment in severely sick children aged 1 month to 5 years in Malawi (SugarFACT): a pragmatic, randomised controlled trial. Issue 12 (December 2020) - Baker, Tim; Ngwalangwa, Fatsani; Masanjala, Henderson; Dube, Queen; Langton, Josephine; Marrone, Gaetano; Hildenwall, Helena
Summary: Background: Low blood glucose concentrations are common in sick children who present to hospital in low-resource settings and are associated with increased mortality. The cutoff blood glucose concentration for the diagnosis and treatment of hypoglycaemia currently recommended by WHO (2·5 mmol/L) is not evidence-based. We aimed to assess whether increasing the cutoff blood glucose concentration for hypoglycaemia treatment in severely ill children at presentation to hospital improves mortality outcomes. Methods: We did a pragmatic, randomised controlled trial at two referral hospitals in Malawi. Severely ill children aged 1 month to 5 years presenting to the emergency department with a capillary blood glucose concentration of between 2·5 mmol/L (3·0 mmol/L in severely malnourished children) and 5·0 mmol/L were randomly assigned (1:1) by a computer-generated randomisation sequence, stratified by study site and severe malnutrition, to receive either an immediate intravenous bolus of 10% dextrose at 5 mL/kg followed by a 24-h maintenance infusion of 10% dextrose at 100 mL/kg for the first 10 kg of bodyweight, 50 mL/kg for the next 10 kg, and 20 mL/kg for each subsequent kg of bodyweight (intervention group) or observation for a minimum of 60 min and standard care (control group). Participants and study personnel were not masked to treatment allocation. The primary outcome was all-cause in-hospital mortality, assessed on an intention-to-treat basis. Safety was also assessed in the intention-to-treat population. The study is registered with ClinicalTrials.gov, NCT02989675 . Findings: Between Dec 5, 2016, and Jan 22, 2019, 10 947 children were screened, of whom 332 were randomly assigned, and 322 were included in the final analysis (n=162 in the control group and n=160 in the intervention group). The study was terminated after an interim analysis at 24% enrolment indicated futility. The median age of participants was 2·3 years (IQR 1·4–3·2), 65 (45%) were female, and the baseline characteristics of participants were similar between the two groups. The number of in-hospital deaths from any cause was 26 (16%) in the control group and 24 (15%) in the intervention group, with an absolute mortality difference of 1·0% (95% CI −6·9 to 9·0). Serious adverse events, including hypoglycaemia, hyperglycaemia, convulsions, reduced consciousness, and death, were reported in 47 (29%) children in the control group and 39 (24%) children in the intervention group. Interpretation: Increasing the cutoff blood glucose concentration for hypoglycaemia treatment in severely sick children in Malawi from 2·5 mmol/L to 5·0 mmol/L did not reduce all-cause in-hospital mortality. Our findings do not support changing the cutoff for dextrose administration, and further research on the optimal management of severely ill children who present to the emergency department with low blood glucose concentrations is warranted. Funding: Swedish Research Council and Stockholm Country Council.